Negative active material for secondary battery, method of preparing same, and lithium secondary battery including same
By using microwave calcining process on the surface of the carbon-based material, the problem caused by volume changes in the silicon-based anode material during lithium embedding/deintercalation is solved, and efficient lithium ion conductivity and battery life are achieved.
Patent Information
- Application Number
- CN202411190463.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-31
- Filing Date
- 2024-08-28
- Publication Date
- 2025-05-02
AI Technical Summary
The silicon-based anode material causes volume changes during the intercalation/deintercalation process of lithium, resulting in electrical desorption and reversible capacity loss. The microwave calcination process has problems of uneven formation of silicon nanoparticles and silicon carbide generation.
Silicon-carbon composites are prepared by using microwave calcining process on the surface of carbon-based materials, and the atmosphere, reaction time and raw material particle size are controlled to inhibit the formation of silicon carbide and the ratio of unreacted silicon, and to increase the reaction rate of silicon raw materials.
The capacity and stability of the negative electrode material in lithium secondary batteries are achieved, the generation of unreacted silicon is reduced, the conductivity of lithium ion is improved, and the life of the battery is extended.
Smart Images

Figure CN119920856A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode active material for a secondary battery, a preparation method thereof and a lithium secondary battery comprising the negative electrode active material. Background Art
[0002] Recently, as the demand for electronic devices such as mobile devices has increased, the development of technologies for mobile devices has been launched. As driving power sources for these electronic devices, the demand for lithium secondary batteries such as lithium batteries, lithium ion batteries, and lithium ion polymer batteries has increased significantly. In addition, as automobile fuel consumption and exhaust-related regulations are being strengthened globally, the electric vehicle market is developing rapidly, and it is expected that the demand for medium and large secondary batteries such as secondary batteries for electric vehicles (EVs) and secondary batteries for energy storage devices (ESS) will increase rapidly.
[0003] On the other hand, as the demand for high capacity of secondary batteries such as medium and large secondary batteries is increasing, silicon-based negative electrode materials with excellent theoretical capacity are being studied as negative electrode materials for secondary batteries. However, silicon-based negative electrode materials cause large volume changes during the insertion / extraction of lithium, cause electrical desorption due to pulverization of silicon particles, and have the problem of reversible capacity loss during repeated charge and discharge cycles.
[0004] In order to solve the problem of mechanical damage to the electrode caused by the volume expansion and contraction of silicon and the resulting rapid shortening of life, research is being conducted to improve performance by combining it with a heterogeneous material that can buffer the volume expansion of silicon and by making silicon into nanoparticles. In particular, active development is being carried out in the technical aspects of the composite process for silicon (nano) particles and graphite and in the commercialization of the process cost reduction of silicon nanoparticle preparation.
[0005] The present invention relates to a method for preparing a composite negative electrode material of nano-sized silicon and a carbon-based material by a single process, which provides a method for preparing a silicon-carbon composite in which silicon nanoparticles are formed on a carbon surface by microwaves. The melting point of silicon is 1,414°C, and when it melts, its density increases more than that of a solid, similar to water. Graphite (carbon-based material) has the characteristic of rapidly generating heat when the π electrons present in the structure are alternately induced to negative (-) and positive (+) charges by microwaves (wavelength: 1m to 1mm; frequency: 300MHz to 300GHz). By applying this phenomenon, silicon with a lower melting point than graphite can be melt-processed on the graphite surface, and entropy can be rapidly increased by rapid energy transfer, so that a silicon nanomaterial (graphite of composite nano-silicon) with an increased specific surface area can be prepared on the graphite surface.
[0006] The method for preparing silicon-carbon composites using microwaves is a method that directly transfers energy to the carbon surface. Regardless of the medium that supports the carbon material, the temperature of the carbon itself rises sharply as long as microwaves are irradiated, and it cools down rapidly after the microwave irradiation stops. Compared with existing heating methods, it is more efficient in terms of time and energy, so there is an advantage of being able to reduce manufacturing time and energy costs.
[0007] However, since the energy is only transferred to the part irradiated with microwaves, there is a problem that silicon nanoparticles cannot be uniformly formed on the entire surface of carbon (graphite), or the attached silicon particles are coarsened and thinned. In this case, it is difficult to fully buffer the volume expansion of silicon particles during lithium insertion / extraction.
[0008] In addition, silicon carbide (SiC) synthesized at a high temperature of more than 900°C is generated as a byproduct on the surface of carbon (graphite) that is rapidly heated to about 1400°C by microwaves. This silicon carbide is inert to lithium ions and hinders the diffusion of lithium ions into silicon particles, resulting in problems of reduced capacity and efficiency. Summary of the invention
[0009] Technical problem to be solved by the invention
[0010] The object of the present invention is to provide a composite negative electrode material (silicon-carbon composite) formed by compounding nano-sized silicon and carbon-based materials through a calcination process using microwaves, and a method for preparing a silicon-carbon composite by performing a process for preparing nano-silicon particles and a process for compounding silicon and carbon-based materials as a single process.
[0011] In addition, another object of the present invention is to provide a negative electrode active material having improved capacity characteristics by suppressing the generation of silicon carbide (SiC) which is an inert material.
[0012] In addition, another object of the present invention is to reduce the ratio of unreacted silicon by controlling the production ratio of silicon carbide and silicon nitride as reaction by-products within a specific range.
[0013] In addition, the present invention provides a method for preparing a negative electrode active material, which can control the gas atmosphere, reaction time and average particle size of the raw material within a specific range during the microwave calcination process to suppress the generation of reaction by-products and improve the reaction rate of the silicon raw material.
[0014] Means for solving technical problems
[0015] One embodiment of the present invention provides a negative electrode active material for a secondary battery, comprising: a silicon-carbon composite including a carbon-based material and a first silicon-based nano-coating layer formed on the carbon-based material; silicon carbide; silicon nitride; and second silicon-based particles.
[0016] The above silicon carbide (SiC) and silicon nitride (SiN x ) can be contained in the above-mentioned silicon-based nano-coating or mixed with the above-mentioned silicon-carbon composite.
[0017] The silicon carbide may be contained in the negative electrode active material in an amount of 1 wt % to 30 wt % relative to the total amount of the compound containing the silicon element.
[0018] The silicon nitride may be contained in the negative electrode active material in an amount of 10 wt % to 40 wt % relative to the total amount of the compound containing the silicon element.
[0019] Silicon Nitride (SiN x ) and the weight ratio of the above silicon carbide (SiC) (SiN x / SiC) can be 0.4 to 2.
[0020] The second silicon particles may have an average particle size D 50 The second silicon particles are composed of silicon particles with a size of 0.4 μm to 10 μm, and the content of the second silicon particles can be less than 40 wt % relative to the total amount of the compound containing silicon element.
[0021] The first silicon-based nano-coating layer may include a silicon film with a thickness of 10 nm to 100 nm formed on the surface of the carbon-based material and a particle size D 50 At least one of silicon particles having a size of 10 nm to 100 nm.
[0022] The carbon-based material may be at least one selected from the group consisting of natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers and hard carbon.
[0023] The negative electrode active material may include the carbon-based material and the compound containing the silicon element as a whole in a weight ratio of 5:5 to 9.5:0.5.
[0024] Another embodiment of the present invention provides a method for preparing a negative electrode active material for a secondary battery, which includes: a mixing process of obtaining a mixture by mixing a carbon-based material and a silicon-based material; and a calcination process of irradiating microwaves on the above mixture in a gas atmosphere of N2 greater than 50 volume %.
[0025] In the above mixing process, the above silicon-based material may have an average particle size D 50 The silicon particles are 0.4 μm to 10 μm.
[0026] In the above mixing process, the above carbon-based material may have an average particle size D 50 Carbon-based particles of 5 μm to 30 μm.
[0027] The calcination process may be performed in a gas atmosphere of 80 volume % to 100 volume % N2.
[0028] The calcination process may include irradiating microwaves at a power of 1 kW to 3 kW for 10 seconds to 10 minutes while maintaining the heating temperature of the mixture at 1,100° C. to 1,400° C.
[0029] The preparation method may further include cooling the calcined product to a temperature ranging from -10°C to 10°C.
[0030] Still another embodiment of the present invention provides a negative electrode for a secondary battery including the negative electrode active material and a secondary battery including the negative electrode; a positive electrode; and an electrolyte.
[0031] Effects of the Invention
[0032] According to the present invention, there can be provided a negative electrode active material including a carbon-based material that is heated in a short time when microwaves are irradiated to melt silicon and silicon nanoparticles and a thin film are formed on the surface of the carbon-based material during cooling.
[0033] In addition, according to the present invention, specifically, by performing microwave carbon thermal shock in an N2 atmosphere, the generation of silicon oxide that reduces the heating temperature of the raw material surface to about 900°C is suppressed, so that the heating temperature of the raw material surface can be increased to about 1,200°C, which is the melting point of silicon, in a short time, thereby reducing unreacted silicon or increasing the reaction rate of the silicon raw material. In addition, since SiN generated in an N2 atmosphere x , relatively inhibiting SiC x The generation of SiN x It has the effect of improving lithium ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1a to Figure 1c Surface SEM images of the negative electrode active materials prepared in Examples 1 to 3.
[0035] Figure 2 1 to 3 show the XRD analysis results of the negative electrode active materials prepared in Examples 1 to 3.
[0036] Figure 3a and Figure 3b The SEM-EDS analysis results of the negative electrode active materials prepared in Comparative Example 1 and Example 1 are shown. DETAILED DESCRIPTION
[0037] The advantages and features of the present invention and the methods for achieving them can be clearly seen through the accompanying drawings and the embodiments described in detail below. However, the present invention is not limited to the embodiments disclosed below, but can be implemented in various different forms. The embodiments are only used to fully disclose the present invention so that people with general knowledge in the technical field to which the present invention belongs can fully understand the scope of the invention. The scope of the present invention is determined by the claims of the present invention.
[0038] Unless otherwise specified, all terms (including technical and scientific terms) used in this specification can be used as the meanings that can be commonly understood by people with general knowledge in the technical field to which the present disclosure belongs. Throughout the specification, when a component is referred to as "including (or comprising)" an element, unless otherwise expressly provided, it is replaced by excluding any other elements, which may mean that a component may further include other elements. In addition, unless otherwise specified, nouns in the singular form also include plural forms.
[0039] One embodiment of the present invention provides a negative electrode active material, which includes a silicon-carbon (Si / C) composite having a silicon-based nano-coating formed on a carbon-based material. The negative electrode active material includes: a silicon-carbon composite, including a carbon-based material and a first silicon-based nano-coating formed on the carbon-based material; silicon carbide; silicon nitride; and second silicon-based particles.
[0040] In the first silicon-based nano-coating, by compounding with a carbon-based material capable of buffering the volume expansion of silicon, the problem of mechanical damage to the electrode caused by the volume expansion and contraction of silicon and the resulting rapid shortening of the lifespan can be improved.
[0041] In addition, silicon carbide is a byproduct that does not contribute to capacity and can reduce battery capacity, while silicon nitride can increase the stability of the battery by improving lithium ion conductivity during battery charging and discharging.
[0042] In the present invention, the second silicon-based particles refer to unreacted silicon, i.e., the silicon raw material is not nano-sized after the microwave calcination process and still exists in the form of raw material size (400nm-10um). The volume expansion of the unreacted silicon is not fully buffered during the insertion / deinsertion of lithium, which may cause the volume change of the negative electrode.
[0043] The above silicon carbide (SiC) and silicon nitride (SiN x ) may be contained in the above-mentioned first silicon-based nano-coating layer or mixed with the above-mentioned silicon-carbon composite and contained.
[0044] When the above SiC and SiN xWhen included in the first silicon-based nano coating, the silicon nanoparticles and silicon thin film forms may be mixed and formed into a coating, or the coating may be formed in at least a portion of the silicon nanoparticles or silicon thin film.
[0045] Relative to the total amount of silicon-containing compounds, the content of the above-mentioned silicon carbide can be 1 weight % to 30 weight %, specifically, 1 weight % refers to 25 weight %, 1 weight % refers to 20 weight %, 5 weight % to 20 weight % or 5 weight % to 15 weight %.
[0046] Silicon carbide (SiC) synthesized at a high temperature of more than 900°C and inert to lithium ions can be attached to the surface of the carbon-based material that is rapidly heated to about 1200°C by microwaves. If the content of silicon carbide exceeds the above-mentioned design range, during the microwave calcination reaction, SiO, which is a reaction intermediate of SiO, will reduce the surface heating temperature of silicon and graphite raw materials, so that the reaction is carried out at a temperature lower than the melting point of the silicon raw material, thereby reducing the silicon reaction rate and increasing the generation of SiC. In addition, the generated SiC is a byproduct that does not contribute to the capacity, which has the problem of reducing the battery capacity.
[0047] On the other hand, the silicon-containing compound is a silicon-containing compound contained in the negative electrode active material prepared by microwave calcination reaction, which includes silicon nano-coating, unreacted silicon, silicon carbide and silicon nitride.
[0048] Relative to the total amount of the silicon-containing compound, the content of the silicon nitride may be 10 wt % to 40 wt %, specifically, 10 wt % to 35 wt %, 10 wt % to 30 wt % or 12 wt % to 30 wt %.
[0049] If the silicon nitride content is within the above design range, the capacity will decrease slightly, but an irreversible phase (Li2SiN2) with high lithium ion conductivity will be formed during charging and discharging, thereby improving the life stability.
[0050] Silicon Nitride (SiN x ) and the weight ratio of the above silicon carbide (SiC) (SiN x / SiC) may be 0.4 to 2.5. Specifically, the weight ratio (SiN x / SiC) can be 0.4 to 2, 0.5 to 2, 0.5 to 1.5 or 0.5 to 1. x / SiC) exceeds the design range, then SiN x The ratio of SiN x The total amount of SiC generated tends to increase rapidly, which may lead to deterioration of capacity characteristics. x / SiC is lower than the design range, then SiNx The total amount of SiC generated is reduced, but the unreacted silicon (second silicon particles) is increased, which may reduce the total silicon reaction rate (silicon nanocrystallization).
[0051] The second silicon particles may have an average particle size D 50 It is composed of silicon particles with a size of 0.4 μm to 10 μm.
[0052] The second silicon particles are particles in the form of a raw material size of 0.4 μm to 10 μm that cannot be nano-sized even after the microwave calcination process, and may include unreacted silicon. The second silicon particles are not included in the first silicon nano-coating layer, and therefore exist in a state of being simply mixed with the silicon-carbon composite, and may cause a volume change of the negative electrode during battery operation.
[0053] Relative to the total amount of the compound containing the silicon element, the content of the second silicon particles may be less than 40 wt %, for example, 5 wt % to 40 wt %, 5 wt % to 30 wt % or 5 wt % to 20 wt %.
[0054] If the content of the second silicon particles exceeds the upper limit, the ratio of unreacted silicon increases, making it difficult to buffer the volume expansion of silicon during battery operation, resulting in a volume change of the negative electrode and a decrease in battery life characteristics. On the contrary, if the content of the second silicon particles is lower than the lower limit, the specific gravity of graphite may be too high, or byproducts such as SiN and SiC may increase, resulting in deterioration of capacity characteristics.
[0055] In addition, the second silicon particles may have an average particle size D 50 The unreacted silicon particles have an average particle size D of 0.4 μm to 10 μm, for example. 50 Unreacted silicon particles of 0.4 μm to 5 μm, 0.4 μm to 3 μm, 0.4 μm to 2 μm, 0.4 μm to 1 μm, 0.4 μm to 0.9 μm, 0.4 μm to 0.8 μm, 0.4 μm to 0.7 μm, 0.4 μm to 0.6 μm or 0.4 μm to 0.5 μm.
[0056] The average particle size D of the second silicon particles as unreacted silicon 50 Corresponding to the average particle size D of silicon raw material 50 Therefore, the average particle size D of the second silicon particles is 50 The smaller the average particle size of the second silicon particles, the more favorable it is for improving the silicon reaction rate, but it will promote the formation of SiC and SiN. Conversely, the larger the average particle size of the second silicon particles, the lower the silicon reaction rate.
[0057] The carbon-based material may be at least one selected from the group consisting of natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers and hard carbon, for example, preferably natural graphite or artificial graphite. In addition, the carbon-based material may be a single particle or a secondary particle formed by aggregation of multiple particles.
[0058] In addition, the carbon-based material may have an average particle size D 50 The carbon-based particles are 5 μm to 30 μm, 5 μm to 20 μm or 10 μm to 20 μm, and the average particle size D 10 Carbon-based particles and / or an average particle size D of 3 μm to 20 μm, 3 μm to 15 μm or 5 μm to 15 μm 90 Carbon-based particles of 15 μm to 35 μm, 15 μm to 30 μm or 20 μm to 25 μm.
[0059] In addition, the above-mentioned carbon-based materials can be spherical, plate-shaped, or needle-shaped particles. Like plate-shaped and needle-shaped particles, the propagation path of microwaves can be expanded by adjusting the structure of the material (porous, hollow, core-shell, multi-layer and hierarchical), thereby further improving the absorption capacity of the microwave absorber.
[0060] In addition, the conditions for controlling the heating of carbon-based materials by microwaves include the type, content and particle shape of the carbon-based materials. If the type, average particle size and morphology of the carbon-based materials fall within the scope of the present invention, the microwave absorption capacity can be improved.
[0061] The first silicon-based nano-coating layer may include a silicon film with a thickness of 10 nm to 100 nm and a particle size D selected from the group consisting of: 50 At least one of silicon particles having a size of 10 nm to 100 nm.
[0062] It is preferred to increase the ratio of molten silicon attached to the surface of carbon-based particles in the form of nanoparticles and prevent the coarsening of silicon particles and the connection between particles (silicon thin film). If the attached silicon particles are coarsened / thinned, it may be difficult to fully buffer the volume expansion of silicon particles during the insertion / desorption of lithium. Therefore, preferably, the first silicon-based nano-coating layer includes a particle size D in a higher content (weight or volume) than the silicon thin film with a thickness of 10nm to 100nm. 50 Silicon particles with a size of 10nm to 100nm.
[0063] The silicon (Si) particles may have an average particle size D of 10 nm to 100 nm or 20 nm to 100 nm. 50 , and preferably has a spherical shape.
[0064] On the other hand, the sizes (average particle diameters) of the above-mentioned silicon nanoparticles, second silicon-based particles, carbon-based materials, etc. may refer to sizes D respectively measured by cumulative volume. 50 In this specification, unless otherwise defined, D 50 It refers to the average size of the diameter of the pores that represent 50% of the cumulative volume in the particle size distribution. Average size D 50 The average size D can be measured by methods known to those skilled in the art, for example, using a transmission electron microscope (TEM) photograph or a scanning electron microscope (SEM) photograph. As another method, the average size D can be calculated by measuring with a dynamic light scattering measuring device, analyzing the data, and counting the number of pores in each pore size range. 50 value.
[0065] Relative to the total weight of the silicon-carbon composite, the content of the first silicon-based nano-coating layer may be 1 wt % to 50 wt %, for example, 1 wt % to 40 wt %, 1 wt % to 30 wt %, 5 wt % to 30 wt %, or 5 wt % to 20 wt %. In addition, the first silicon-based nano-coating layer may be formed to have a thickness of 10 nm to 200 nm, for example, 10 nm to 180 nm, 10 nm to 160 nm, 10 nm to 150 nm, or 10 nm to 130 nm.
[0066] The silicon-carbon composite may further include a carbon coating on the first silicon-based nanocoating. By minimizing direct exposure of silicon in the first silicon-based nanocoating to the electrolyte, electrolyte side reactions may be reduced, and the volume expansion of silicon particles may be further buffered, thereby improving the life characteristics of the battery. The carbon coating may be formed to have a thickness of 0.01 μm or more, for example, may be formed to have a thickness of 0.03 μm or more or 0.05 μm or more and 10 μm or less, 5 μm or less, or 1 μm or less. Thus, the above effects may be further improved.
[0067] Next, a method for preparing a negative electrode active material for a secondary battery is provided, which may be the method for preparing the negative electrode active material according to one embodiment of the present invention.
[0068] The preparation method of the negative electrode active material for a secondary battery includes: a mixing process of obtaining a mixture by mixing a carbon-based material and a silicon-based material; and a calcining process of irradiating microwaves on the mixture in a gas atmosphere containing more than 50% by volume of N2.
[0069] The above-mentioned mixing process is a step of mixing the carbon-based material and the silicon-based material to obtain a mixture in which silicon-based particles are dispersed on the surface of the carbon-based material.
[0070] The mixing may be performed using a particle mixer at 500 to 2,000 RPM or 700 to 1,500 RPM for 1 to 10 minutes. As the particle mixer, a self-rotating stirrer, a revolving stirrer, a blade stirrer, or a particle fusion machine may be used, but the present invention is not limited thereto.
[0071] In addition, as the above-mentioned mixing, the carbon-based material and the silicon-based particles may be mixed in a weight ratio of 99:1 to 60:40, 99:1 to 70:30, 95:5 to 70:30, or 95:5 to 80:20.
[0072] The carbon-based material may be selected from natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers, hard carbon or a combination thereof. The carbon-based material may have an average particle size D 50 The carbon-based particles are 5 μm to 30 μm, 5 μm to 20 μm or 10 μm to 20 μm.
[0073] The silicon-based material may have an average particle size D 50 Silicon particles with an average particle size of 0.4 μm to 10 μm, for example 50 The average particle size D of the silicon raw material is 0.4 μm to 5 μm, 0.4 μm to 3 μm, 0.4 μm to 2 μm, 0.4 μm to 1 μm, 0.4 μm to 0.9 μm, 0.4 μm to 0.8 μm, 0.4 μm to 0.7 μm, 0.4 μm to 0.6 μm or 0.4 μm to 0.5 μm. 50 The smaller the average particle size, the more favorable it is to improve the silicon reaction rate, but it may promote the formation of SiC and SiN. Conversely, the larger the average particle size, the lower the silicon reaction rate.
[0074] The above-mentioned microwave calcination process is a step of using microwaves to quickly heat the surface of the carbon-based material in a mixture of carbon-based (raw material) material and silicon-based (raw material) material, melting the silicon-based material through the microwave-heated carbon-based material, thereby forming a first silicon-based nano-coating on the surface of the carbon-based material.
[0075] The microwave calcination process is carried out in a gas atmosphere containing more than 50% by volume of N2, for example, in a gas atmosphere containing more than 90% by volume of N2 or in a gas atmosphere containing 100% by volume of N2.
[0076] If microwave calcination is performed in a N2 gas atmosphere, oxidation of silicon-based materials and carbon-based materials can be prevented, so that the surface heating temperature of the carbon-based materials can be quickly raised to the melting point of silicon. Therefore, the silicon reaction rate can be increased, and the SiN byproduct can be promoted compared to the SiC byproduct.x The generation of can improve capacity degradation and enhance lithium ion conductivity.
[0077] In addition, N2 gas is more likely to decompose when irradiated with microwaves, and it is easy to generate SiN x On the contrary, when an inert gas such as Ar is used, neither oxygen nor nitrogen is contained in the gas, so the production amounts of SiN and SiC are reduced, and the microwave calcination reaction product, i.e., the silicon-based compound, is produced only in a pure silicon state, which may be disadvantageous in terms of life characteristics and particle and negative electrode stability according to the contraction and expansion of silicon particles.
[0078] The microwave heating may be performed by irradiating microwaves (wavelength: 1 m to 1 mm; frequency: 300 MHz to 300 GHz) at a power of 1 kW to 3 kW for 10 seconds to 10 minutes, 30 seconds to 2 minutes, or 30 seconds to 60 seconds.
[0079] With the increase of microwave output and irradiation time, the silicon reaction rate and SiN x The amount of silicon produced increases, which may help improve the lifespan, but the actual content of silicon active material will decrease, resulting in deterioration of capacity characteristics.
[0080] In addition, the microwave heating may heat the surface of the carbon-based material to 1,200° C. or higher within 1 minute, for example, within 40 seconds or within 10 seconds.
[0081] As a result, when the thawing (melting) temperature of the silicon-based raw material is reached, the interface temperature between the carbon-based material and silicon reaches above the melting point of silicon, thereby increasing the silicon reaction rate. At this time, the SiN x production.
[0082] After the microwave calcination step, a cooling step may be further included to prevent the crystallinity of the silicon-based material attached to the surface from increasing due to the heat energy remaining in the carbon-based material. The cooling step may be performed at room temperature or at a temperature of -10°C to 10°C and at normal pressure, preferably in a cooled reactor injected with nitrogen.
[0083] Still another embodiment of the present invention provides a negative electrode for a secondary battery and a secondary battery including the negative electrode active material.
[0084] The negative electrode includes a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and the negative electrode active material according to one aspect of the present invention is present in the negative electrode active material layer.
[0085] There is no particular limitation on the negative electrode current collector, as long as it has conductivity without causing chemical changes in the battery, and examples thereof may include stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc. In addition, the negative electrode current collector may generally have a thickness of 3 μm to 500 μm, or may increase the binding force of the negative electrode active material by forming micro-concave and convex on the surface of the current collector. For example, the negative electrode current collector may be provided in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, a nonwoven body, etc.
[0086] The negative electrode active material layer may be a layer containing the above-mentioned negative electrode active material, a conductive material and a binder.
[0087] The above-mentioned conductive material is used to impart conductivity to the electrode, and can be used without restriction as long as it does not cause chemical changes in the negative electrode active material and has conductivity. Non-limiting examples of conductive materials include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. Typically, the content of the conductive material can be 1% to 30% by weight based on the total weight of the negative electrode active material layer.
[0088] The above-mentioned binder is a material that plays a role in improving the adhesion between multiple negative electrode material particles and the bonding force between the negative electrode active material and the collector. Non-limiting examples of binders include: polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers. Generally, the content of the binder can be 1% to 30% by weight relative to the total weight of the negative electrode active material layer.
[0089] In addition to using the above-mentioned negative electrode active material, the negative electrode according to one embodiment of the present invention can be prepared according to a conventional method for preparing a negative electrode for a secondary battery. For example, the negative electrode can be prepared by applying a slurry for forming a negative electrode active material layer to a negative electrode collector, and then drying and rolling it, wherein the slurry includes a negative electrode active material and a selective binder and a conductive material. According to another example, the negative electrode can be prepared by casting a slurry for forming a negative electrode active material layer on a separate carrier, and then laminating a thin film obtained by stripping the negative electrode active material layer from the carrier on the negative electrode collector.
[0090] According to another aspect of the present invention, an electrochemical device comprising the above negative electrode is provided, wherein the electrochemical device may be a battery, a capacitor, etc., more specifically, a lithium secondary battery.
[0091] The secondary battery includes a negative electrode, a positive electrode positioned opposite to the negative electrode, and a separator and an electrolyte (electrolyte) between the negative electrode and the positive electrode. In addition, the lithium secondary battery may include a battery container (housing) that accommodates an electrode assembly including a positive electrode, a negative electrode and a separator, and a sealing member that seals the battery container.
[0092] Among them, according to the shape of the battery container (shell), lithium secondary batteries can be divided into can-type lithium secondary batteries and pouch-type lithium secondary batteries. The above-mentioned can-type lithium secondary batteries have a can form in which the electrode assembly is enclosed in a metal can, and the above-mentioned pouch-type lithium secondary batteries have a pouch form in which the electrode assembly is enclosed in a bag made of a sheet material such as an aluminum laminate.
[0093] Hereinafter, the present invention will be described in more detail with reference to examples, however, these examples are only used to illustrate the present invention in more detail, and the scope of the present invention should not be construed as being limited to the following examples.
[0094] Example
[0095] (Example 1)
[0096] Natural graphite and plate-like silicon particles (D 50 :400nm) powders were charged into a super mixer at a weight ratio of 9:1 and mixed at 1,000 rpm for 10 minutes.
[0097] The mixture was irradiated with microwaves (2,450 MHz, 1 kW power, irradiation time: 40 seconds) while the surface temperature of the mixture was maintained at 1,200°C in an atmosphere of N2 1 atm.
[0098] Next, cooling was performed at -5°C / min, thereby preparing a negative electrode active material including a silicon-carbon composite having a silicon nanocoating layer formed on natural graphite.
[0099] A negative electrode slurry was prepared by dispersing 30 g of 96 wt % of the prepared silicon-carbon composite, 1 wt % of carbon black, 1.5 wt % of an SBR binder, and 1.5 wt % of carboxymethyl cellulose in distilled water. The prepared negative electrode slurry was uniformly coated on a copper film and vacuum dried at 135° C., thereby preparing a negative electrode for a lithium secondary battery.
[0100] 94 wt% LiNi 0.9 Co 0.1 Mn 0.1 O2 (NCM911, EcoPro BM), 3 wt% carbon black and 3 wt% PVdF binder were mixed in N-methyl-2-pyrrolidone to prepare positive electrode slurry. The prepared positive electrode slurry was evenly coated on an aluminum film, vacuum dried at 135°C, and then rolled to prepare a positive electrode for a lithium secondary battery.
[0101] The prepared positive and negative electrodes and a porous polyethylene film (Celgard 2300, thickness: 25 μm) separator were placed in a battery container, and a lithium secondary battery was manufactured using an electrolyte containing LiPF6 at a concentration of 1.15 M in a solvent mixed with EC:EMC at a volume ratio of 3:7.
[0102] (Examples 2 and 3)
[0103] In addition to using D 50 is 2 μm (Example 2) and D 50 A negative electrode active material, a negative electrode and a lithium secondary battery were prepared in the same manner as in Example 1 except that the plate-like silicon particle powder was 10 μm (Example 3).
[0104] (Example 4 and Comparative Example 1)
[0105] A negative electrode active material, a negative electrode and a lithium secondary battery were prepared in the same manner as in Example 1, except that microwave calcination was performed in a gas atmosphere as shown in Table 2 below.
[0106] (Examples 5 to 8)
[0107] A negative electrode active material, a negative electrode and a lithium secondary battery were prepared in the same manner as in Example 1, except that microwave calcination was performed within the microwave (MW) time (seconds) shown in Table 4 below.
[0108] Experimental example
[0109] Experimental Example 1. Confirmation of the shape and composition of negative electrode active material particles by SEM images and XRD analysis Figure 1a to Figure 1c Surface SEM images of the negative electrode active materials prepared in Examples 1 to 3.
[0110] Reference Figure 1a to Figure 1cIt can be confirmed that a silicon-carbon composite having a silicon nano-coating mixed in the form of a thin film and particles and unreacted silicon not attached to the graphite surface is formed on the surface of natural graphite.
[0111] Figure 2 1 is to show the XRD analysis results of the negative electrode active material prepared in Example 1.
[0112] XRD analysis was performed using D8 ADVANCE A25 of Bruker Corporation, and was measured by applying a current of 30 mA at a voltage of 45 kV.
[0113] Depend on Figure 2 The analysis results confirmed the peaks of all material compositions corresponding to Si, SiC, Si3N4 and graphite crystals.
[0114] Experimental Example 2. Analysis of the surface heating temperature of raw materials according to the type of atmosphere gas in the calcination process
[0115] Table 1 shows the exothermic temperature of the surface of the natural graphite raw material measured in the microwave calcination process of Example 1 and Comparative Example 1. At this time, the exothermic temperature is the temperature measured in real time on the sample surface when the microwave irradiation time reaches 40 seconds.
[0116] Table 1
[0117] Comparative Example 1 Example 1 Atmosphere gas Air 1atm <![CDATA[N2 1atm]]> Fever temperature 950℃ 1200℃
[0118] According to analysis, when microwave carbon thermal shock is performed in an oxygen-containing air atmosphere in Comparative Example 1, SiC is formed by the following reaction formula in the process of increasing the reaction rate (nano-siliconization) of the silicon raw material by adjusting the microwave treatment time / power, etc.
[0119] SiO2(s)+C(s)→SiO(g)+CO(g)……(1)
[0120] SiO(g)+2C(s)→SiC(s)+CO(g)……(2)
[0121] SiO(g)+3CO(g)→SiC(s)+2CO2(g)……(3)
[0122] Referring to reaction formula (1), silicon oxide reacts with graphite at a high temperature of about 900°C or above to generate SiO and CO gas. Referring to reaction formula (2), SiO gas reacts with graphite to generate SiC core. Referring to reaction formula (3), SiO gas and CO gas formed in reaction formulas (1) and (2) react to grow SiC crystals.
[0123] The microwave absorptivity of silicon oxide formed in Comparative Example 1 is low, so the surface heating temperature of natural graphite and silicon raw material is reduced, which becomes a factor in increasing unreacted silicon. In addition, silicon carbide produced from silicon oxide is a byproduct that does not contribute to capacity and reduces battery capacity.
[0124] On the other hand, when microwave carbon thermal shock is performed in the N2 atmosphere of Example 1, the generation of silicon oxide can be suppressed, so that the surface heating temperature of the raw material can be increased to the silicon melting point of about 1200°C in a short time to reduce unreacted silicon. In addition, the silicon nitride generated in the N2 atmosphere forms an irreversible phase (Li2SiN2) with high lithium ion conductivity during the charge and discharge of the battery, thereby having the effect of improving the life stability.
[0125] Experimental Example 3. Analysis of SiN, SiC, Si content and silicon reaction rate of negative electrode active material particles
[0126] (SiN, SiC, Si content evaluation method)
[0127] The SiN content is a numerical value (weight %) expressed by converting the mass ratio of N measured by ONH analysis into Si3N4, and the SiC and Si contents are numerical values (weight %) expressed by converting the XRD peak area (deconvolution of the XRD peak) into a mass ratio. The results are shown in Tables 2 to 4 below.
[0128] (Silicon Reactivity Evaluation Method)
[0129] Unreacted silicon refers to the silicon raw material used in the mixing process which has not been nano-sized after the microwave calcination process and still exists in a raw material size of 400nm to 10μm. Nanosilicon refers to the silicon raw material used in the mixing process that reacts and is deposited on the carbon surface in the form of spheres and thin films with a size of 50nm to 100nm.
[0130] The negative electrode active materials prepared in Comparative Example 1 and Example 1 were subjected to SEM-EDS analysis, and the results are as follows: Figure 3a and Figure 3b shown.
[0131] The silicon particle size distribution before and after the microwave calcination process was analyzed in Examples 1 to 8 and Comparative Example 1, and the size of the unreacted silicon (D 50 The silicon reaction rate (%) was calculated by comparing the area increase and decrease of the particle size peak of (=400nm~10um). The results are shown in Tables 2 to 4 below.
[0132] Table 2
[0133]
[0134] As shown in Table 2, the SiNx When comparing Example 1 and Example 4, the higher the nitrogen partial pressure in the atmosphere gas, the higher the Si3N4 content ratio, and the silicon reaction rate increases.
[0135] Table 3
[0136]
[0137] It can be seen from Table 3 that regardless of the size of the silicon raw material, the Si3N4 / SiC ratio remains unchanged, and the larger the size of the silicon raw material, the smaller the silicon reaction rate.
[0138] Table 4
[0139]
[0140] It was confirmed that as the microwave irradiation time increased, the generation of SiC was suppressed and the silicon reaction rate increased. These results show that, as described above, when the generation of silicon oxide is suppressed, the surface heating temperature of natural graphite can be raised to the silicon melting point of about 1,200°C in a short time, thereby increasing the silicon reaction rate and reducing the unreacted silicon content.
[0141] However, if the MW irradiation time is excessively increased, the Si3N4 / SiC ratio increases, the total amount of Si3N4 and SiC increases, and the capacity reduction may increase.
[0142] As described above, although the present invention has been illustrated and described with respect to specific embodiments, it is obvious to those skilled in the art that various modifications and changes can be made to the present invention without departing from the technical concept of the present invention provided in the appended claims.
Claims
1. A negative electrode active material for a secondary battery, characterized in that: include: A silicon-carbon composite, comprising a carbon-based material and a first silicon-based nano-coating layer formed on the carbon-based material; Silicon carbide; Silicon nitride; and Second silicon-based particles.
2. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The silicon carbide (SiC) and silicon nitride (SiN x ) is contained in the silicon-based nano-coating or mixed with the silicon-carbon composite.
3. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The content of the silicon carbide is 1 wt % to 30 wt % relative to the total amount of the compound containing silicon element.
4. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The content of the silicon nitride is 10 wt % to 40 wt % relative to the total amount of the compound containing silicon element.
5. The negative electrode active material for a secondary battery according to claim 1, characterized in that: Silicon Nitride (SiN x ) to the weight ratio of the silicon carbide (SiC) (SiN x / SiC) is 0.4 to 2.
6. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The second silicon particles have an average particle size D 50 The second silicon particles are composed of silicon particles with a size of 0.4 μm to 10 μm, and the content of the second silicon particles is less than 40 wt % relative to the total amount of the compound containing silicon element.
7. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The first silicon-based nano-coating layer comprises a silicon film with a thickness of 10 nm to 100 nm and a particle size D 50 At least one of silicon particles having a size of 10 nm to 100 nm.
8. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The carbon-based material is at least one selected from the group consisting of natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers and hard carbon.
9. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The negative electrode active material includes the carbon-based material and the compound containing the silicon element as a whole in a weight ratio of 5:5 to 9.5:0.
5.
10. A method for preparing a negative electrode active material for a secondary battery, characterized in that: include: A hybrid process, in which a carbon-based material and a silicon-based material are mixed to obtain a hybrid; and The calcination process comprises irradiating the mixture with microwaves in a gas atmosphere containing more than 50% by volume of N2.
11. The method for preparing a negative electrode active material for a secondary battery according to claim 10, characterized in that: In the mixing process, the silicon-based material has an average particle size D 50 The silicon particles are 0.4 μm to 10 μm.
12. The method for preparing a negative electrode active material for a secondary battery according to claim 10, characterized in that: In the mixing process, the carbon-based material has an average particle size D 50 Carbon-based particles of 5 μm to 30 μm.
13. The method for preparing a negative electrode active material for a secondary battery according to claim 10, characterized in that: The calcination process is performed in a gas atmosphere of 80 volume % to 100 volume % of N2.
14. The method for preparing a negative electrode active material for a secondary battery according to claim 10, characterized in that: The calcination process is to irradiate microwaves at a power of 1 kW to 3 kW for 10 seconds to 10 minutes while maintaining a heat generation temperature of the mixture at 1,100° C. to 1,400° C.
15. The method for preparing a negative electrode active material for a secondary battery according to claim 10, characterized in that: The method further comprises cooling the calcined product to a temperature ranging from -10°C to 10°C.
16. A negative electrode for a secondary battery, characterized in that: The negative electrode active material according to claim 1 is included.
17. A secondary battery, characterized in that: The method comprises the negative electrode according to claim 16; a positive electrode; and an electrolyte.